Ultima ratio Principle in the Criminalization of Tax Evasion - Dobrovolskis, Martynas (Teisė, 2020)
This article evaluates the significance of the principle of ultima ratio for the national process of criminalization. It also assesses the criminalization of tax evasion in the Criminal Code of the Republic of Lithuania using the criminalization criteria established in both national and international legal regulation, case law and criminal law doctrine.
Keywords: tax evasion; tax avoidance; criminal law; criminalization